The performance of investment newsletters - Jaffe, Jeffrey F.; Mahoney, James M. (Journal of Financial Economics, 1999)
This paper analyzes the recommendations of common stocks made by the investment newsletters followed by the Hulbert Financial Digest. We conclude that, taken as a whole, the securities that newsletters recommend do not outperform appropriate benchmarks. Our data provide modest evidence that the future performance of a newsletter is related to its past performance, when performance is measure by raw returns. Evidence of persistence vanishes, however, when performance is measured by abnormal returns. We find little, if any, evidence of herding, i.e., cross-sectional dependence of recommendations, across newsletters. Newsletters tend to recommend securities that have performed well in the recent past. Finally, newsletters with poor past performance are more likely to go out of business.